THE OPTIMATION OF CELLULASE ENZYME OF MOLD ISOLATED FROM AGRICULTURE LAND IN WUKIRSARI AFTER MERAPI ERUPTION - Umniyatie, Siti; Rakhmawati, Anna; Yulianti, Evy (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2015)
The aim of this study was to develop potency of mold isolated from agriculture land after Merapi eruption in 2010 at Wukirsari, Cangkringan, Sleman, Yogyakaerta. The treatment were temperature and pH optimation to the cellulase enzyme activity and the protein level yield by mold isolate A 2.10, A 2.15 and B 3.18 in different substrate, avicel and carboxymethyl cellulose (CMC). This study was experimental study to find out the substrate, pH and temperature which yield the best activity and protein level from mold isolate A 2.10, A 2.15 dan B 3.18. the population of this study all of the crude enzymes from mold isolate, and the sample was 1 ml of crude enzyme which treated with different substrate, pH and temperature. The result of this study showed that the best susbtrate was avicel and the optimum temeperature and pH for isolate A.2.10 was 25 ⁰C Keywords: optimation, cellulase enzyme, cellulolytic